Empathy and respect among other values: analysis of collaborative teaching experiences with social organizations - Flores Águila, Melissa Andrea (2020)
In this article, four learning and service experiences (ApS) developed between 2016 and 2019 were analyzed, with the aim of identifying the implications of this educational strategy in the values growth of future professionals. Through a qualitative methodology, which incorporated documentary analysis and focus group discussions, the perceptions of students and academics from the Occupational Therapy program who participated in these experiences were identified. It is evident that, in the territory, it is where the enclave of fundamental values occurs to exercise the future profession, the community agent being a fundamental actor in the training process. The territorial intervention made it possible to strengthen the promotion of values such as empathy, respect, equality and equal opportunities. The training process makes sense if it is carried out in collaboration with the territory, identifying problems and seeking solutions to overcome them, thus generating co-responsibility and social ethics.